ORAL HYGIENE STATUS AND PERIODONTAL TREATMENT NEEDS AMONG THE ELDERLY PEOPLE IN THE GLANTANGAN PLANTATION AREA JEMBER - Melok Aris Wahyukundari; Yuliana Mahdiyah Daat Arina; Zea Anggieta Putri Sunardi (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: The aging process leads to several physical changes in the elderly. These include changes in periodontal tissues and decreased musculoskeletal function. These changes reduce the ability of older people to clean the oral cavity, increasing the risk of periodontal disease in older adults. Purpose: This study aims to describe the oral hygiene status and periodontal treatment needs of the elderly in the Glantangan Plantation Area, Jember. Methods: This is a descriptive observational study with a purposive sampling technique conducted on 98 older adults aged 60-74 years in three villages of Glantangan Plantation Area Jember who fulfilled the inclusion and exclusion criteria. Oral hygiene status was examined using the OHI-s, and periodontal treatment needs were examined using the CPITN. Results: The mean age of the respondents was 66 ± 4.11 years, with the majority being female (90.82%). The mean OHI-s score was 4.62±0.95, and most older people had poor oral hygiene (81%). 49% of the elderly had a CPITN score of 3, and 7.1% had a CPITN score of 4. The most common periodontal treatment needs of older people in the Glantangan Plantation Area are improving personal oral hygiene and professional scaling and root planing (93%). Conclusion: The oral hygiene status of older individuals in the Glantangan Plantation Area is poor, with periodontal treatment needs including personal oral hygiene improvement, scaling and root planing, and complex periodontal treatment.